Small mammal populations and plant community succession at artesian well sites in Great Sand Dunes National Park, Colorado - Garza, Sarah Julía, author; Bowser, Gillian, advisor; Wilson, Kenneth R., advisor; Doherty, Paul F., committee member; Paschke, Mark, committee member (Colorado State University. Libraries, 2013)
For more than 100 years, artificial artesian wells in the San Luis Valley of south-central Colorado have been a steady source of water for livestock and wildlife on lands administered by Great Sand Dunes National Park and The Nature Conservancy. In summer 2011, a study was established to examine effects on local biota of capping the artesian wells in 2010. In Chapter 1, I focused on the short-term effects of capping artesian well sites and the effects on the population dynamics and species diversity of small mammals. In 2011 and 2012, I compared newly capped well sites, well sites with water, and reference sites by estimating density (Program DISTANCE), survival (Cormack-Jolly-Seber Model in Program MARK), species occupancy (Robust Occupancy Model in Program MARK), and measures of species diversity (species richness, Shannon-Weiner index, and species evenness) of small mammals. I modeled small mammal density and survival as a function of well site type, percent plant cover, disturbance level from ungulates, and year of study using an information theoretic approach to rank models and estimate the relative importance of the independent variables. Over the two years, I captured 1,150 individuals of 6 rodent species; however, only two species, Ord's kangaroo rat (Dipodomys ordii) and Apache or plains pocket mice (Perognathus sp.), had sufficient numbers for density and survival analyses. There was no significant difference in density and survival estimates for these species at the well types; however species occupancy estimates varied by well type and by species such that open well sites had the greatest probability of occupancy of the deer mouse (Peromyscus maniculatus), and reference sites had the greatest probability of occupancy of the thirteen-lined ground squirrel (Spermophilus tridecemlineatus). For the kangaroo rat density and survival, the type of well site was important with greatest values at capped well sites. For pocket mice, the disturbance level by ungulates and year of study were important predictors of density and survival; density was negatively correlated with amount of disturbance and survival nearly doubled from 2011 to 2012. Richness, the Shannon-Weiner diversity index and community evenness values were greatest at reference sites. Results suggest that in the short term, small mammal density and survival does not increase after a well is capped, species occupancy is variable, and diversity does not change. Additional studies are needed to provide a better understanding of the long-term changes in small mammal population dynamics and biodiversity as capped well sites continue to revert to habitats similar to reference sites. In Chapter 2, I concentrated on the short-term effects of capping wells on the plant community with a focus on secondary ecological succession. I characterized the habitats at sampled sites by identifying plant species (native and exotic) and examining potential sources of variation by modeling plant cover and species frequency as a function of variables such as well site type, the ungulate disturbance level, distance from well heads, and the year of study. I used an information theoretic approach to rank models and estimate the relative importance of these independent variables. I also estimated indices of native species diversity including richness, Shannon-Weiner diversity index, Simpson's index, community evenness, and compared patterns of plant form cover (i.e., shrubs, forbs, and grasses) at increasing distances from well heads. Year of study and distance from well heads were important predictors of native plant cover and exotic plant cover, respectively; however there was no difference in native or exotic plant cover based on well status (open or closed). Well site type, year of study, and ungulate disturbance intensity levels were important predictor variables for native species frequency whereas for exotic species frequency, well type was important. All indices of species diversity values were greatest at the reference sites. Capped well sites had varying distance patterns across different plant forms whereas all plant cover was highest at the farthest distances from open well heads. Overall, this study suggested that while plant communities at well sites are not significantly different after capping the well head, the abundant exotics may need additional control efforts for the community to return to species composition typical of the sand sheet ecosystem.
Keywords: capture-recapture; model selection; small mammals; species diversity; succession